Humanitarian Price Of Technological Progress: Main Outlines Of The Research - Boronenko, Vera; Mensikovs, Vladimirs (European Scientific Journal, ESJ, 2016)
The article is worked out with support of the Marie Curie FP7- PEOPLE-2011-COFUND program - NEWFELPRO (The new International Fellowship Mobility Programme for Experienced Researchers in Croatia) within the project Â«Rethinking Territory Development in Global Comparative Researches (Rethink Development)Â», Grant Agreement No. 10. Current decline in competitiveness of many highly developed capitalist countries with innovation-driven economy stimulates scientists to find explanations for this by rethinking territory developmentâ€™s conceptual framework. Based on relevant publications of A.Toffler (1970, 1980), Ch.Murray (2003), G.Easterbrook (2004), R.Wright (2004), own research findings as well as ideas of Development Economics and Philosophy of Technology, the research hypothesis is as follows: territory development in the modern world declines when humanitarian price of technological progress begins to outweigh benefits, and this price determines different paths of development for concrete territories. Scientific approach proposed for using in this research is based on the fundamental economic Law of Diminishing Marginal Productivity applied for technological progress and humanitarian price of the progress in different parts of the world, which are perceived â€“ based on the conception of F.Braudel â€“ as â€œworlds-economiesâ€. Therefore, the main objective of this article is to outline key elements and tasks of the further empirical and econometrical researches aiming to propose a relevant methodology and techniques of measuring humanitarian price of technological progress for different territories as well as to define mechanisms to reduce this price in existed â€œworlds-economiesâ€.